Implementasi Business Intelligence Menggunakan Tableau dalam Analisis Kasus Kematian Akibat Penyakit Demam Berdarah Dengue - Gilang, Oprin Muhammad; Irwansyah, Irwansyah (TIN: Terapan Informatika Nusantara, 2025)
Dengue Hemorrhagic Fever (DHF) remains one of the most serious infectious diseases in Indonesia, particularly in the West Java Province. The high population density, combined with environmental conditions that support the proliferation of dengue virus-carrying mosquitoes, has led to the continuous emergence of cases each year. Based on data analysis, during the period from 2014 to 2023, a total of 225,481 deaths caused by DHF were recorded in this province. When categorized by gender, the number of male fatalities reached 117,107 cases, while female deaths amounted to 108,374 cases. Among all regions, Bandung City and Bogor City recorded the highest numbers of fatalities, with 54,900 deaths in Bandung and 23,802 in Bogor during the same period. One of the obstacles faced in efforts to manage DHF is the lack of informative, concise, and easily accessible data for various relevant stakeholders. In fact, such information is crucial as a basis for determining more targeted disease prevention and control strategies. In response to this situation, this study seeks to offer a solution by applying the concept of Business Intelligence (BI) through the use of Tableau software to visualize mortality data related to DHF. The process begins with an Extract, Transform, Load (ETL) stage applied to secondary data obtained from the Satu Data Indonesia portal, involving a total of 540 data records on DHF deaths. This is followed by analysis and presentation in the form of an interactive dashboard. The visualization results are displayed using various types of charts, including geo mapping, line charts, horizontal bar charts, stacked bar charts, and pie charts. Each visualization provides clearer insights into the annual trends of DHF cases, distributions by gender, and the geographical spread of fatalities across all regions in West Java. In conclusion, the implementation of Tableau within the Business Intelligence framework has proven effective in processing and simplifying initially complex data into visual information that is easier to interpret. Furthermore, these visualizations can serve as a valuable reference for data-driven decision-making processes, particularly in supporting the prevention and control efforts of DHF cases in the West Java Province.